Associations of Ureaplasma urealyticum infection with male infertility and intrauterine insemination outcomes - Wan, Yang-Yang; Shi, Xiao-Yun; Liu, Wen-Jing; Bai, Shun; Chen, Xin; Li, Si-Yao; Jiang, Xiao-Hua; Wu, Li-Min; Zhang, Xian-Sheng; Hua, Juan (Asian journal of andrology, 2025)
Abstract Ureaplasma urealyticum (UU) is one of the most commonly occurring pathogens associated with genital tract infections in infertile males, but the impact of seminal UU infection in semen on intrauterine insemination (IUI) outcomes is poorly understood. We collected data from 245 infertile couples who underwent IUI at The First Affiliated Hospital of USTC (Hefei, China) between January 2021 and January 2023. The subjects were classified into two groups according to their UU infection status: the UU-positive group and the UU-negative group. We compared semen parameters, pregnancy outcomes, and neonatal birth outcomes to investigate the impact of UU infection on IUI outcomes. There were no significantly statistical differences in various semen parameters, including semen volume, sperm concentration, total and progressive motility, sperm morphology, leukocyte count, the presence of anti-sperm antibody, and sperm DNA fragmentation index (DFI), between the UU-positive and UU-negative groups of male infertile patients (all P > 0.05). However, the high DNA stainability (HDS) status of sperm differed between the UU-positive and UU-negative groups, suggesting that seminal UU infection may affect sperm nuclear maturation (P = 0.04). Additionally, there were no significant differences in pregnancy or neonatal birth outcomes between the two groups (all P > 0.05). These results suggest that IUI remains a viable and cost-effective option for infertile couples with UU infection who are facing infertility issues.